Second site [broadcast towers]. (IEEE spectrum)
Multiple broadcast towers, once thought a waste of money, are now the order of the day. Following the terrorist attacks at the World Trade Center on 9/11, All broadcasts ceased minutes after impact, and as the city tried to discover what was going on, just one television station reappeared to fill the void. WCBS-TV was the only station that had transmitters at both the World Trade Center and the Empire State Building. Generally stations have backup transmitters and often antennas, but they are always at the same tower. Now all area broadcasters, and to some extent their network parents, want what was once thought unnecessary: having backup antennas and transmitters at more than one tower. While most New York area broadcasters are sending signals from the Empire State Building at reduced power, a group of TV stations is searching for a site for a new tower. The site that best meets the broadcasters' three criteria is on Governors Island, just off the southern tip of Manhattan. The US federal government, which at present owns the island, is transferring the property to New York City. But the city's mayor does not want a tower there.